Oxidative stability of smoked chicken sausage substituted with red palm mid fraction during chilled storage - Alina A.R.; Siti Mashitoh A.; Babji A.S.; Maznah I.; Syamsul K.M.W.; Muhyiddin Y. (2024)
Indexed by Scopus